Evidence for altered insulin receptor signaling in Alzheimer's disease. (1st July 2018) - Griffith, Chelsea M.; Eid, Tore; Rose, Gregory M.; Patrylo, Peter R.
Abstract: Epidemiological data have shown that metabolic disease can increase the propensity for developing cognitive decline and dementia, particularly Alzheimer's disease (AD). While this interaction is not completely understood, clinical studies suggest that both hyper- and hypoinsulinemia are associated with an increased risk for developing AD. Indeed, insulin signaling is altered in post-mortem brain tissue from AD patients and treatments known to enhance insulin signaling can improve cognitive function. Further, clinical evidence has shown that AD patients and mouse models of AD often display alterations in peripheral metabolism. Since insulin is primarily derived from the periphery, it is likely that changes in peripheral insulin levels lead to alterations in central nervous system (CNS) insulin signaling and could contribute to cognitive decline and pathogenesis. Developing a better understanding of the relationship between alterations in peripheral metabolism and cognitive function might provide a foundation for the development of better treatment options for patients with AD. In this article we will begin to piece together the present data defining this relationship by briefly discussing insulin signaling in the periphery and CNS, its role in cognitive function, insulin's relationship to AD, peripheral metabolic alterations in mouse models of AD and how information from these models helps understand the mechanisms through which these changes potentially lead to impairments in insulin signaling in the CNS, and potential ways to target insulin signaling that could improve cognitive function in AD. This article is part of the Special Issue entitled 'Metabolic Impairment as Risk Factors for Neurodegenerative Disorders.' Highlights: Metabolic disease increases the risk of developing cognitive decline and dementia. AD is associated with peripheral metabolic alterations. Insulin/insulin sensitivity is altered in the AD brain. Insulin and Insulin sensitizers can improve cognitive function in AD.